Experimental and Numerical Investigation of Composite Phase Change Materials for Building Energy Saving - Zhang, Guanhua; Guo, Yuqian; Liu, Zhiqiang; Lu, Wei; Yan, Xiaoyu; Du, Yanping (Frontiers in Energy Research, 2021)
Composites composed of paraffin wax and copper foam with porosity of 95 % and pore density of 15 ppi, 30 ppi, and 50 ppi were prepared by the melt impregnation method. Two building models of the same size were made using gypsum board. The roof of the experimental model was covered with 50ppi copper foam /paraffin composite phase change board, and the roof of the reference model was covered with foam insulation board. The heat transfer experiment was conducted with a constant heat flux. EnergyPlus software was also employed to simulate the energy saving effects of the building models. The size and material of the model established during the simulation are consistent with the experimental model. Experimental results showed that the phase change composite board delayed the highest indoor temperature for 1.5 h, and it also reduced the indoor maximum temperature by 1.2° and the indoor energy consumption by 21 %. The simulation results showed that the phase change composites board delayed the appearance of the highest indoor temperature by 1.3 h and reduced the highest indoor temperature by 1.1°C, and the maximum indoor energy consumption decreased by 19 %. The copper foam/paraffin composite material can effectively improve the thermal comfort and reduce the energy consumption of the building model.